Pharmacokinetic properties of peptidic radiopharmaceuticals: reduced uptake of (EH)3-conjugates in important organs - Eder, Matthias; Löhr, Thomas; Bauder-Wüst, Ulrike; Rebert, Markus; Mier, Walter; Schäfer, Martin; Haberkorn, Uwe; Eisenhut, Michael (Journal of nuclear medicine, 2013)
The translation of radiolabeled tumor-targeting peptides into clinical routine is often hampered by an enhanced accumulation into the excreting organs. It has recently been reported that the (EH)3 purification tag is able to improve the biodistribution of Affibody molecules. Therefore, the aim of this study was to prove the positive influence of (EH)3 on the biodistribution of 2 peptidic radiopharmaceuticals, Glu-urea-Lys(Ahx)-HBED-CC and TATE-PEG2-HBED-CC (HBED-CC is N,N′-bis [2-hydroxy-5(carboxyethyl)benzyl] ethylenediamine-N,N′- diacetic acid, TATE is octreotate, and PEG2 is 8-amino-3,6-dioxaoctanoic acid spacer). Methods: Both compounds were compared with their respective (EH)3-conjugated variants in cell-based in vitro assays and organ distribution. Results: The introduction of (EH)3 to HBED-CC significantly changed the biodistribution profiles. In both cases, the uptake in several organs was reduced whereas tumor uptake was not affected. Most importantly, (EH)3 lowered the kidney and liver uptake of the prostate-specific membrane antigen inhibitor each by a factor of 2.8 and, in the case of octreotate, the liver accumulation by a factor of 51. Conclusion: The biodistribution data suggest that (EH)3 is able to improve the pharmacokinetic properties of peptidic radiopharmaceuticals, leading to reduced uptake in organs such as the liver, an important site of metastatic disease.